Análise proteômica e potencialidades de proteínas e peptídeos da fração caseínica de leite caprino - Barbosa, Paula Perazzo de Souza (2019)
Goat milk is an important protein-rich food matrix that may present important functional properties in both nutritional and pharmaceutical areas. The objective of this study was to characterize the proteins present in the casein fraction (FCN) of goat milk, to obtain bioactive peptides from the FCN through in vitro hydrolysis with enzymes pepsin and trypsin; and to test the biological potential of the FCN and its peptides. For this, goat milk was collected in three distinct postpartum periods: 4 ± 2 days (colostrum); 28 ± 2 (peak lactation); and 120 ± 2 (mature milk). Then, it was skimmed by centrifugation and subjected to isoelectric precipitation by addition of hydrochloric acid to pH 4.1. The precipitate, corresponding to the FCN, was washed with distilled water, solubilized with sodium hydroxide to determine the proteins soluble by the Bradford method, dialysed against in cellulose membrane (cut-off 14 kDa), frozen and lyophilized. Partial chemical characterization composition and SDS-PAGE of the FCNs were made, which were subsequently submitted to the nLC-ESI-MS/MS technique. The FCN of milk collected from goats with 28 ± 2 days of lactation was hydrolyzed with pepsin followed by trypsin. The FCN of mature milk was characterized by means of two-dimensional electrophoresis, regarding the amino acid profile and antinociceptive activity. Subsequently, it was hydrolyzed with pepsin and trypsin, separately. The peptide profile was identified by Tris-Tricine electrophoresis. The hydrolysates had their biological potential evaluated by means of antibacterial activity for Staphylococcus aureus, Escherichia coli, Listeria monocytogenes, Salmonella spp and Pseudomonas aeroginosa; and antioxidant by the ABTS, DPPH and FRAP methods. The results of this study show that the casein fraction of goat milk is rich in proteins and changes its protein profile during lactation according to the nutritional needs of the puppy. Some proteins found, mainly in the mature milk fraction, can expose new biotechnological approaches as anticancer potential. The FCN of mature milk shows antinociceptive activity, and essential and non-essential amino acids, with high content of glutamic acid, followed by proline. Both the hydrolyzate of the proteins present in the FCN of the milk collected from goats with 28 ± 2 days of lactation and those of the FCN of the mature milk have peptides with antimicrobial properties. FCN hydrolysates of mature milk also have antioxidant properties. Thus the goat milk proteins are an interesting opportunity for application as antimicrobial agents and natural antioxidants that can be used for therapeutic purposes.